Soil physical properties under different land uses in Universiti Putra Malaysia, Selangor - Abdul Malik, Mohammad Nazrin; Abdu, Arifin; Karam Singh, Daljit Singh; Jusop, Shamshuddin; Karim, Md. Rezaul; Abdul Hamid, Hazandy; Jamaluddin, Aiza Shaliha; Rajoo, K. S.; Patek Mohd, Nur Nazirah (Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2015)
Assessing land use-induced changes in soil properties are essential for addressing issues of agro-ecosystem transformation and sustainable land productivity. Therefore, it could be concluded that results from these sites were influenced by the weathering of the parent materials, human activities, and vegetation and it is required to employing integrated soil fertility management in sustainable manner to optimize and maintain the favorable soil physicochemical properties.